New Alzheimer models for drug screening based on improved human amyloid beta (1‐42) oligomer preparations. (1st February 2022) - Colin, Julie; Allouche, Ahmad; Hidalgo, Sophie; Lager, Estelle; Lemoine, Sandrine; Muller, Christophe; Rozan, Pascale; Bisson, Jean‐François; Violle, Nicolas
Abstract: Background: The etiology of Alzheimer's disease (AD) is poorly understood. A growing body of literature suggests that amyloid beta oligomers (AβO) as the root cause of this disease. Here, we describe new translational in vitro and in vivo models of AD, induced by minute amount of in‐house preparation of human AβO. Method: AβO were reproducibly prepared from human Aβ 1‐42 monomers. Rodent primary neurons were used to assess the neurotoxic activities of AβO in vitro and elderly wild‐type mice administered by a single intracerebral injection AβO in vivo. Result: The oligomeric preparations were characterized by SDS‐page, electron microscopy and dot‐plot tests. In vitro, AβO induced a dose‐dependent neurodegeneration on rodent primary neurons based on various read‐outs. Interestingly, neurotoxicity was greater with AβO than fibrillar Aβ, while Aβ monomers did not induce any neuronal damage. AβO‐induced neurotoxicity was significantly attenuated by brain‐derived neurotrophic factor (BDNF). In vivo, a single intracerebral microinjection of AβO in 18‐month‐old wild‐type mice, led to a significant memory impairment, synaptic loss in hippocampus and increased secretion of brain proinflammatory cytokines 15 days post administration. Moreover, the memory deficits were significantly reversed with Donepezil used as reference drug. Conclusion: In conclusion, we characterized new tools for drug screening based on the soluble AβO hypothesis of AD. In vivo, this new non‐inherited Alzheimer model can be used both to evaluate disease modifying and symptomatic drugs. Finally, these models are also valuable tools to understand the mechanisms underlying AD.